The Effect of Storage Time of Water Hyacinth Liquid Organic Fertilizer on Microorganism Viability and Potency - Yun Sondang; Trisia Wulantika; Ramond Siregar (Jurnal Penelitian Pendidikan IPA, 2024)
The quality of biological organic fertilizer is determined by the viability of microorganisms during storage until the fertilizer is applied to the field. The purpose of this study was to determine the effect of length of storage of biological organic fertilizer on the viability of microorganisms, and identify the types of microorganisms that can survive in several storage periods and their potential. The research was conducted at the Payakumbuh State Agricultural Polytechnic Screenhouse from September to November 2024 using a non-factorial Completely Randomized Design (CRD) with five treatments and five replications. The treatment of storage duration of biological organic fertilizer includes: T1 = 0 days storage time, T2 = 7 days storage time, T3 = 14 days storage time, 21 days storage time, and 28 days storage time. The results showed that the best storage length for bacterial viability was from 0 to 14 days after fermentation with a bacterial population of 1.0,107-3.3,107 CFU/ml and a fungal population of <10-1.4,102 CFU/ml. Seven potential and multifunctional bacterial isolates were found, B. altitudinis, Bacillus cf. zanthoxylli, Bacillus cereus, Pseudomonas aeruginosa, Pseufomonas. flexibilis, Pseudomonas cf. pharmacofabricae, and Ectopseudomonas mendocina. All bacterial isolates were able to produce IAA hormone with concentrations between 0.0039-0.0057 µg/ml. Bacterial species that have high viability in water hyacinth POH are bacteria from the genera Bacillus spp. and Pseudomonas spp.